Osteogenesis imperfecta: Novel genetic variants and clinical observations from a clinical exome study of 54 Indian patients. (7th August 2020) - Madhuri, Vrisha; Selina, Agnes; Loganathan, Lakshmi; Kumar, Ashis; Kumar, Vignesh; Raymond, Renita; Ramesh, Sowmya; Vincy, Nimmy; Joel, Giftson; James, Deeptiman; Kandagaddala, Madhavi; B, Antonisamy
Abstract: Osteogenesis imperfecta (OI) is a group of inherited disorders with increased bone fragility and wide genetic heterogeneity. We report the outcome of clinical exome sequencing validated by Sanger sequencing in clinically diagnosed 54 OI patients in Indian population. In 52 patients, we report 20 new variants involving both dominant and recessive OI‐specific genes and correlate these with phenotypes. COL1A1 and COL1A2 gene variants were identified in 44.23%, of which 28.84% were glycine substitution abnormalities. Two novel compound heterozygous variants in the FKBP10 gene were seen in two unrelated probands. A novel heterogeneous duplication of chromosomal region chr17: 48268168–48278884 from exons 1–33 of the COL1A1 gene was found in one proband. In five probands, there were additional variants in association with OI. These were ANO5 in association with CRTAP in two probands of the same family causing gnathodiaphyseal dysplasia, COL5A2 with LEPRE1 causing Ehlers Danlos syndrome, COL11A1 in addition to COL1A1 causing Stickler syndrome, and a previously unreported combination of SLC34A1 gene variant with FKBP10 leading to Fanconi renal tubular syndrome type II. Our findings demonstrate the efficacy of clinical exome sequencing in screening OI patients, classifying its subtypes, and identifying associated disorders in consanguineous populations.